2023
DOI: 10.1200/jco.23.00933
|View full text |Cite
|
Sign up to set email alerts
|

Practical Assessment and Management of Vulnerabilities in Older Patients Receiving Systemic Cancer Therapy: ASCO Guideline Update

Abstract: PURPOSE To update the ASCO guideline (2018) on the practical assessment and management of age-associated vulnerabilities in older patients undergoing systemic cancer therapy. METHODS An Expert Panel conducted a systematic review to identify relevant randomized clinical trials (RCTs), systematic reviews, and meta-analyses from January 2016 to December 2022. RESULTS A total of 26 publications met eligibility criteria and form the evidentiary basis for the update. RECOMMENDATIONS The Expert Panel reiterates its o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(55 citation statements)
references
References 85 publications
0
36
0
Order By: Relevance
“…A CGA is a multidimensional process to identify medical, social, and functional needs and is associated with chemotherapy-related toxic effects, functional decline, and mortality . By performing a pretreatment CGA, physicians may facilitate nononcologic interventions or individualize treatment plans, thereby likely reducing the risk of toxic effects and possibly improving QOL . Previous trials showed that a GA-based intervention could reduce chemotherapy-related toxic effects and early treatment discontinuation compared with usual care …”
Section: Discussionmentioning
confidence: 99%
“…A CGA is a multidimensional process to identify medical, social, and functional needs and is associated with chemotherapy-related toxic effects, functional decline, and mortality . By performing a pretreatment CGA, physicians may facilitate nononcologic interventions or individualize treatment plans, thereby likely reducing the risk of toxic effects and possibly improving QOL . Previous trials showed that a GA-based intervention could reduce chemotherapy-related toxic effects and early treatment discontinuation compared with usual care …”
Section: Discussionmentioning
confidence: 99%
“…Cognitive assessment as part of age-friendly healthcare aligns with the holistic assessment of older adults with cancer. The recently updated ASCO guidelines for older adults with cancer include recommendations for a practical geriatric assessment (GA) [26]. Recommendation 2.1 'A GA should include high priority ageing-related domains known to be associated with outcomes in Adapted from [13].…”
Section: Mentationmentioning
confidence: 99%
“…older adults with cancer to include assessment of physical and cognitive function, emotional health, comorbid conditions, polypharmacy, nutrition, and social support' [26,27]. Screening for cognitive impairment, delirium and depression, depending on the healthcare setting is a vital part of adequate GA and implementation of AFHS [20,28].…”
Section: Mentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 presents the summary of the updated guideline recommendations addressed in this article; the complete recommendations appear in the full guideline update (cite new GA guideline). 5…”
Section: Question 1: What Are the Changes To The Updated Ga Guideline?mentioning
confidence: 99%